Cockle Shell as an Additive in Pavement Mixture - Zaini, Muhammad Zulhakimi Hakim; Muhammad Alif Syahmi Mohd Zin; Muhammad Afiq Azemi; Khairul Zaman Abdul Malek (Multidisciplinary Applied Research and Innovation, 2023)
Considering cockle shell (CS) was rich in calcium oxide (CaO), it can impact the behaviour and qualities of pavement, this paper investigates the usage of CS as an addition in premix mixtures. Restaurant waste cockle shells (WCS) collected from seafood dishes may pollute the environment and cause pain to the nearby community. The main purpose of this study is to create a pavement mix by using       10 g, 20 g and 30 g of CS as an addition in a mix design that meets specified parameters. Specific gravity tests, voids tests, stability tests and stiffness tests were performed. The outcomes were compared depending on the mix design. It's fascinating to learn that the chemical composition of CS has an impact on specific gravity, voids, stability and stiffness on pavement mixture. 10 g of CS is an ideal amount as an additive in pavement mixture in term of density, stability and stiffness compared to control samples. CS is strongly suggested for future research as a premix mixture component.